Epigenetic regulation of the tumor microenvironment: A leading force driving pancreatic cancer - Vera, Renzo (2024)
Dysregulation of the epigenomic landscape of tumor cells has been implicated in the pathogenesis of pancreatic cancer. However, these alterations are not only restricted to neoplastic cells. The behavior of other cell populations in the tumor stroma such as cancer-associated fibroblasts, immune cells, and others are mostly regulated by epigenetic pathways. Here, we present an overview of the main cellular and acellular components of the pancreatic cancer tumor microenvironment and discuss how the epigenetic mechanisms operate at different levels in the stroma to establish a differential gene expression to regulate distinct cellular phenotypes contributing to pancreatic tumorigenesis.